Connexin36 expression in major centers of the auditory system in the CNS of mouse and rat: Evidence for neurons forming purely electrical synapses and morphologically mixed synapses. (10th September 2015) - Rubio, M.E.; Nagy, J.I.
Highlights: Cx36 is widely expressed in the auditory system of rat and mouse. Neuronal gap junctions composed of Cx36 are abundant in the auditory system. Auditory nuclei contain nerve terminals forming morphologically mixed synapses. Nerve terminals associated with Cx36 in the cochlear nucleus are of primary afferent origin. Abstract: Electrical synapses formed by gap junctions composed of connexin36 (Cx36) are widely distributed in the mammalian central nervous system (CNS). Here, we used immunofluorescence methods to document the expression of Cx36 in the cochlear nucleus and in various structures of the auditory pathway of rat and mouse. Labeling of Cx36 visualized exclusively as Cx36-puncta was densely distributed primarily on the somata and initial dendrites of neuronal populations in the ventral cochlear nucleus, and was abundant in superficial layers of the dorsal cochlear nucleus. Other auditory centers displaying Cx36-puncta included the medial nucleus of the trapezoid body (MNTB), regions surrounding the lateral superior olivary nucleus, the dorsal nucleus of the medial lemniscus, the nucleus sagulum, all subnuclei of the inferior colliculus, and the auditory cerebral cortex. In EGFP-Cx36 transgenic mice, EGFP reporter was detected in neurons located in each of auditory centers that harbored Cx36-puncta. In the ventral cochlear nuclei and the MNTB, many neuronal somata were heavily innervated by nerve terminals containing vesicular glutamate transporter-1 (vglut1) and Cx36 was frequently localized at these terminals. Cochlear ablation caused a near total depletion of vglut1-positive terminals in the ventral cochlear nuclei, with a commensurate loss of labeling for Cx36 around most neuronal somata, but preserved Cx36-puncta at somatic neuronal appositions. The results suggest that electrical synapses formed by Cx36-containing gap junctions occur in most of the widely distributed centers of the auditory system. Further, it appears that morphologically mixed chemical/electrical synapses formed by nerve terminals are abundant in the ventral cochlear nucleus, including those at endbulbs of Held formed by cochlear primary afferent fibers, and those at calyx of Held synapses on MNTB neurons.